The Dark Energy Survey Supernova Program: slow supernovae show cosmological time dilation out to z ∼ 1. - White, R. M.T.; Davis, T. M.; Lewis, G. F.; Brout, D.; Galbany, L.; Glazebrook, K.; Hinton, S. R.; Lee, J.; Lidman, C.; Möller, A.; Sako, M.; Scolnic, D.; et al. (Oxford University Press (OUP), 2024)
We present a precise measurement of cosmological time dilation using the light curves of 1504 Type Ia supernovae from the Dark Energy Survey spanning a redshift range 0.1 z 1.2. We find that the width of supernova light curves is proportional to (1 + z), as expected for time dilation due to the expansion of the Universe. Assuming Type Ia supernovae light curves are emitted with a consistent duration Δtem, and parametrizing the observed duration as Δtobs = Δtem(1 + z)b, we fit for the form of time dilation using two methods. First, we find that a power of b ≈ 1 minimizes the flux scatter in stacked subsamples of light curves across different redshifts. Secondly, we fit each target supernova to a stacked light curve (stacking all supernovae with observed bandpasses matching that of the target light curve) and find b = 1.003 ± 0.005 (stat) ± 0.010 (sys). Thanks to the large number of supernovae and large redshift-range of the sample, this analysis gives the most precise measurement of cosmological time dilation to date, ruling out any non-time-dilating cosmological models at very high significance.
Keywords: cosmology: observations; transients: supernovae